Primary Care Physicians’ Perceptions of the Challenges and Barriers in the Timely Diagnosis, Treatment and Management of Fibromyalgia - Nandini Hadker; Suchita Garg; Arthi B Chandran; Sheila M Crean; Michael McNett; Stuart L Silverman (Pain Research and Management)
OBJECTIVES: To describe beliefs and practice patterns of primary care physicians (PCPs) providing fibromyalgia (FM) care, and to characterize differences between PCPs who report being able to provide timely and beneficial care versus the remaining PCPs.